Comparison between minimal stitch hernioplasty and continuous suturing of mesh in inguinal hernia repair: a randomised controlled trial - S., Vidhya Sree; Palit, Sandhya; Giridharan, Bhanumati; M., Dinesh; A., Balasubramanian (International Surgery Journal, 2023)
Background: Inguinal hernia repair is the most commonly done surgery of all general surgical procedures. Hence in an attempt to decrease the pain and increase the patient’s comfort, various techniques have been considered to fix the mesh. The aim of this study was to compare the differences between the two techniques of mesh fixation namely the minimal stitch method and the continuous suturing in terms of various parameters. Methods: This study was conducted selecting 126 patients who attended the general surgery OPD at ESIC MC and PGIMSR and randomly allocating them to the two study groups; the patients were followed up till 6 months post-operatively. The parameters taken into account were: the operative time, the duration of hospital stay, the pain scores at various time intervals (POD 1, 3, 7, 30, 60, 90, 180) and the incidence of complications if any. Results: Among the 126 male patients enrolled in the study, the highest % belonged to the age group 51-60. 90% of them had unilateral hernias. The pain scores were significantly low in the minimal stitch group from the first postoperative day up to 1 month. The operative time and duration of hospital stay was also significantly decreased in the minimal stitch group. Conclusions: Hence, the minimal stitch technique used for inguinal hernia repair in our study proved to be comparable to the conventional suturing, better than the latter in terms of patients’ subjective satisfactory factors such as less operative time and less hospital stay while having no significant difference in terms of occurrence of chronic inguinodynia or any other postoperative complications.